2013
DOI: 10.1080/09670874.2013.845321
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that rodent control strategies ought to be improved to enhance food security and reduce the risk of rodent-borne illnesses within subsistence farming villages in the plague-endemic West Nile region, Uganda

Abstract: Rodents pose serious threats to human health and economics, particularly in developing countries where the animals play a dual role as pests: they are reservoirs of human pathogens, and they inflict damage levels to stored products sufficient to cause food shortages. To assess the magnitude of the damage caused by rodents to crops, their level of contact with humans, and to better understand current food storage and rodent control practices, we conducted a survey of 37 households from 17 subsistence farming vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…Mirroring results reported from a previous survey in other villages in the West Nile Region, 46 our study showed that most villagers recognize rodents in their homes to be a concern and are using available methods to reduce their abundances. However, based on survey responses and the abundance of rats trapped within homes, the existing methods are clearly inadequate for eliminating rodents entirely or, perhaps, even for reducing numbers in any significant way.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Mirroring results reported from a previous survey in other villages in the West Nile Region, 46 our study showed that most villagers recognize rodents in their homes to be a concern and are using available methods to reduce their abundances. However, based on survey responses and the abundance of rats trapped within homes, the existing methods are clearly inadequate for eliminating rodents entirely or, perhaps, even for reducing numbers in any significant way.…”
Section: Discussionsupporting
confidence: 60%
“…However, their use has decreased considerably largely because of the risk of food theft. 39,46 Interestingly, although granary usage was reportedly low, our study showed that it was more common in case villages than in control villages. It is unclear whether case villages simply have more stored food than control villages, thus justifying granary use, or if granaries, which are constructed of locally available materials and often are not rodent proof, may concentrate rodents in the home environment and contribute to plague risk.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Trapping and poisoning are done in a reactive rather than preventive fashion and mainly undertaken through individual rather than collective initiative. This is likely to have minimal effects due to rapid recolonization as opposed to preventive and coordinated control at household, compound, or village level 5153. The frequent requests for help or advice on rodent control received during fieldwork was an indication of the overwhelmingly pernicious influence rodents had on everyday life and the difficulty of controlling them.…”
Section: Discussionmentioning
confidence: 99%
“…Most residents of this region live on incomes which fall below the poverty line and rely on subsistence agriculture to make a living (Lakwo et al 2008). Poor housing construction allows easy access to stored foods and hinders efforts to eliminate rodents from the home environment (Eisen et al 2013, 2014). As a result, recent plague control efforts have focused largely on reducing fleas (both on- and off-host) within huts.…”
mentioning
confidence: 99%